2023
DOI: 10.1111/jnc.15880
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of CaV1.3 L‐type calcium channels by Shank3

Qian Yang,
Tyler L. Perfitt,
Juliana Quay
et al.

Abstract: Clustering of L‐type voltage‐gated Ca2+ channels (LTCCs) in the plasma membrane is increasingly implicated in creating highly localized Ca2+ signaling nanodomains. For example, neuronal LTCC activation can increase phosphorylation of the nuclear CREB transcription factor by increasing Ca2+ concentrations within a nanodomain close to the channel, without requiring bulk Ca2+ increases in the cytosol or nucleus. However, the molecular basis for LTCC clustering is poorly understood. The postsynaptic scaffolding pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…This leads us to a comparison of putative protein interactions on the proximal versus extended (full-length) CTT to relate our overall findings to possible clustering mechanisms. The extended CTT of Ca V 1.3 42 contains binding sites for JPH2, AKAP family and PDZ-binding proteins, which are relevant scaffolds for LTCC and may spatially define cluster nanodomains or mediate channel tethering (Choi et al, 2022; Sahu et al, 2019; Stanika et al, 2016; Yang et al, 2023). While these interactions may enhance clustering, none of them appear to be strictly required for clustering, given that we showed cluster formation for the short CTT sequence of Ca V 1.3 42A .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This leads us to a comparison of putative protein interactions on the proximal versus extended (full-length) CTT to relate our overall findings to possible clustering mechanisms. The extended CTT of Ca V 1.3 42 contains binding sites for JPH2, AKAP family and PDZ-binding proteins, which are relevant scaffolds for LTCC and may spatially define cluster nanodomains or mediate channel tethering (Choi et al, 2022; Sahu et al, 2019; Stanika et al, 2016; Yang et al, 2023). While these interactions may enhance clustering, none of them appear to be strictly required for clustering, given that we showed cluster formation for the short CTT sequence of Ca V 1.3 42A .…”
Section: Discussionmentioning
confidence: 99%
“…LTCC form subdiffraction-sized clusters, which facilitate calcium release, cooperative gating and protein interactions (Dixon et al, 2022). Previous studies on Ca V 1.3 clustering in neurons showed that alternative splicing affects Ca V 1.3 function and cluster formation possibly through C-terminal protein interactions with Calmodulin (CaM; Moreno et al, 2016), PDZ-binding proteins (Jenkins et al, 2010; Stanika et al, 2016; Yang et al, 2023) and Junctophilin isoforms (Sahu et al, 2019). These findings point towards analogous modulatory mechanisms governing Ca V 1.3 channel function in cardiomyocytes.…”
Section: Introductionmentioning
confidence: 99%